The COVID-19 pandemic impact on the Polish medical personnel work: a survey and in-depth interviews study - Przyłęcki, Paweł; Wieczorkowska, Magdalena; Pawlak-Kałuzińska, Agnieszka; Cedrowska-Adamus, Wioletta; Gulczyńska, Ewa (Frontiers in Public Health, 2023)
Objective The objective of the study was to examine the impact of the COVID-19 pandemic on the work of medical personnel in terms of: task scope, preparation to perform medical tasks related to the pandemic, team collaboration, involvement in tasks performed, concerns about performing tasks related to the pandemic, stress levels. Methods The mixed-method approach was applied to this cross-sectional study. The online questionnaire which included 40 questions was completed via Google among medical personnel in Poland. Eight semi-structured, in-depth interviews were conducted to deepen the data obtained with the questionnaires. Participants The questionnaire was completed by 215 healthcare professionals, with the largest group being nurses (56.3%) followed by physicians (22.3%), midwives (11.6%) and other healthcare professionals (e.g., physiotherapists, paramedics, nutritionists – 9.8%). Among the respondents were people who worked in the hospital in the so-called “covid wards” (31.2%) and other hospital wards (60%) as well as people who were employed outside the hospital (8.8%). Results The pandemic affected the nature and range of tasks performed by health professionals. Initially, respondents felt unprepared to work under pandemic conditions, but over time their ratings increased in all areas studied. More than half of respondents reported no change in interpersonal relationship within the team, but nearly 35% noted a worsening and only one in 10 claimed improvement. Study participants rated their own commitment to tasks slightly higher than that of their colleagues (mean 4.9 and 4.4 respectively) but the overall rating was high. The mean self-rating of work stress increased from 3.7 before the pandemic to 5.1 during the pandemic. Most of the respondents were afraid of transmission of the infection to their relatives. Other fears included the possibility of making a medical error, not being able to help the patient, not having enough personal protective equipment (PPE) and contracting SARS-CoV-2. Conclusion The conducted study revealed that the organization of medical care in the initial period of the pandemic, especially the hospital care of patients infected with SARS-CoV-2, was quite chaotic. The most affected were the people who were transferred to work in the covid wards. Not all medical professionals were prepared to work with the COVID-19 patients, as they lacked experience working in such facilities, especially in intensive care units (ICU). Working under time pressure and under new conditions led mainly to an increase in perceived stress and conflicts between staff.